Study of CP violation in B∓ → Dh∓ (h = K,π) with the modes D → K∓π∓π0, D → π+π-π0 and D → K+K-π0 - Aaij, Roel; Adeva, B.; Adinolfi, M.; Aquines Gutiérrez, Osvaldo; D'Argent, Philippe; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
An analysis of the decays of B∓→DK∓ and B∓→Dπ∓ is presented in which the D meson is reconstructed in the three-body final states K∓π±π0, π+π−π0 and K+K−π0. Using data from LHCb corresponding to an integrated luminosity of 3.0 fb−1 of pp collisions, measurements of several CP observables are performed. First observations are obtained of the suppressed Atwood-Dunietz-Soni decay B∓→[π∓K±π0]Dπ∓ and the quasi-Gronau-London-Wyler decay B∓→[K+K−π0]Dπ∓. The results are interpreted in the context of the unitarity triangle angle γ and related parameters.